AB0903 Is There Any Relationship between the Children Health Assessment Questionnaire (CHAQ) and the European Quality of Life (EUROQOL) in Children Suffering from Chronic Haemophilic Arthropathy?. (10th June 2014) - Medrare, L.; Ngeuleu, A.; Rkain, M.; Bouaddi, I.; Znat, F.; El Kabbaj, S.; Lakhdar, T.; Benslama, I.; Rkain, H.; Allali, F.; Khattab, M.; El Khorassani, M.; et al.
Abstract : Objectives: We aimed to analyze in children suffering from chronic haemophilic arthropathy relation between there functional impact and there quality of life. Methods: Twenty- three children (mean age of 10.9±3.5 years [4-18]) suffering from severe haemophilia (median disease duration of 12 months (6; 18), median diagnosis delay of 0 months (0, 7)) were included. Functional impairment and quality of life were respectively assessed by the Moroccan versions of Children Health Assessment Questionnaire (CHAQ) and the European Quality of Life (the EUROQOL). A statistical analysis was conducted to determine the correlation between these two parameters using the r of Spearman Results: Chronic haemophilic arthropathy affected knee, elbow, ankle and wrist in respectively 50, 27.5, 20 and 2.5%. Median CHAQ was 0.37 (0, 1.25). EUROQOL domains were affected as following: Mobility (69.6%), usual activity (65.2%), self-care (65.2%), anxiety/depression (43.4%) and pain (34.7%) Table 1 summarize correlation between the CHAQ and the 5 domains of EUROQOL. Conclusions: This study suggests that the functional impact of chronic haemophilic arthropathy in children affected by severe hemophilia seems mainly related to the domains of mobility, self-care and usual activity of the EUROQOL. Further studies are required to verify those results. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4867